Knowledge of finance and Attitude associated with Financial Management Housewife - Hariyanti, Siti; Hadady, Hartaty; Amiro, Suratno (Jurnal Manajemen Sinergi, 2024)
ABSTRACTObjective: This study aims to investigate the relationship between financial knowledge, financial attitude, and household financial management practices in South Halmahera Regency. This research serves as financial literacy for the community and aims to develop targeted and effective financial literacy policies and programs in rural areas.Methodology: The research design employs a survey method due to its quantitative approach. Based on calculations using the Slovin's formula, the sample consists of 73 households or housewife selected through purposive sampling. Statistical analysis was conducted using IBM SPSS.Findings: The first, second, and third hypotheses were accepted based on significance levels smaller than the alpha value.Conclusion: This indicates that the better the financial knowledge of household mothers, the greater the potential for effective and responsible financial management in households in Amasing Kali Village. Furthermore, based on the hypothesis testing results, financial attitude influences financial management. This implies that the financial attitude of household mothers in Amasing Kali Village contributes to financial management as household managers.Â